2007
DOI: 10.1016/j.nima.2007.05.184
|View full text |Cite
|
Sign up to set email alerts
|

Single-UV-photon 2-D imaging with multi-GEM detectors

Abstract: The main goal being the construction of large-area, low-cost position-sensitive micropattern gaseous photomultipliers (GPMs) based on gas electron multipliers (GEM) cascades, we have studied the single-photon imaging capabilities of a 4-GEM GPM with a reflective CsI-photocathode deposited on the top surface of the 1st GEM. The charge readout was performed with a simple/economic Wedge and Strip (W&S) readout electrode, using pulses induced through a resistive electrode. We have demonstrated the feasibility of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…In particular, they are frequently used in gas photosensor devices, such as gas photomultipliers (GPMTs), gas electronmultipliers (GEMS), and other micropattern gas devices, to detect the primary or/and secondary scintillation produced in radiation detectors [1][2][3][4][5][6]. However, the transmission of the photoelectrons may be significantly reduced due to backscattering of the photoelectrons in the gas, thus reducing the effective quantum efficiency of the photocathode, an effect which is especially important when the rate of elastic scattering is high, as in the noble gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they are frequently used in gas photosensor devices, such as gas photomultipliers (GPMTs), gas electronmultipliers (GEMS), and other micropattern gas devices, to detect the primary or/and secondary scintillation produced in radiation detectors [1][2][3][4][5][6]. However, the transmission of the photoelectrons may be significantly reduced due to backscattering of the photoelectrons in the gas, thus reducing the effective quantum efficiency of the photocathode, an effect which is especially important when the rate of elastic scattering is high, as in the noble gases.…”
Section: Introductionmentioning
confidence: 99%
“…Author to whom any correspondence should be addressed 4. Also at: Servic ¸o de Radioterapia, Hospital da Universidade de Coimbra, 3000-075 Coimbra, Portugal 5. Also at: Instituto Superior de Engenharia de Coimbra, 3030-199 Coimbra, Portugal.…”
mentioning
confidence: 99%
“…Having a small size detector sensitive volume requires having a high multiplication gain to achieve a reasonable signal to noise ratio. It has been shown that using a multiple‐GEM arrangement (for different applications) has the advantage of increase in gain without impractical high voltage across the THEGM . Hence, the double‐THGEM arrangement was assembled using the MILPLEX THGEMs and the detector response was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…With the advent of GEMs, they have been widely used for a variety of applications . Particularly, for microdosimetry, Farahmand developed a mini multielement TEPC based on GEM .…”
Section: Introductionmentioning
confidence: 99%